VCSEL Technology for Green Optical Interconnects - A. Kasukawa (IEEE Photonics Journal)
State-of-the-art vertical-cavity surface-emitting laser (VCSEL) technology will be reviewed in terms of power consumption and reliability to realize the energy-efficient high-performance computing (HPC) and data centers. Intermediate wavelength (between short and long wavelength) VCSELs emitting at 1060 nm are promising candidates for the upcoming higher performance computing with energy saving.